Persistence of a mixed lactic acid bacterial starter culture during lysine fortification of sourdough breads by addition of pistachio powder. (April 2020) - Gaglio, Raimondo; Alfonzo, Antonio; Barbera, Marcella; Franciosi, Elena; Francesca, Nicola; Moschetti, Giancarlo; Settanni, Luca
Abstract: Pistachio powder was added to flour or semolina to evaluate its contribution to increase the amount of lysine in bread. Bread production was carried out by sourdough technology using a selected 3-species ( Lactobacillus sanfranciscensis / Leuconostoc citreum / Weissella cibaria ) lactic acid bacterial (LAB) starter culture. All sourdoughs were subjected to a long-time fermentation (21 h) and showed levels of LAB around 10 9 CFU/g, indicating the suitability of pistachio powder for lactic fermentation. Yeasts were also detected, in particular in semolina trials. MiSeq Illumina technology was applied to investigate the bacterial composition of sourdoughs evidencing a different distribution of LAB species among the trials with Lactobacillus as major LAB group in almost all sourdoughs. Physicochemical parameters were comparable among the trials. After baking, pistachio powder was found not to influence the height of the breads, but pistachio breads were more firm than control breads. Color of the breads, void fraction and cell density, were influenced by pistachio powder. The amount of lysine increased consistently thanks to pistachio supplementation which also determined a higher presence of o-xylene, p -cymene and limonene and the appearance of α-pinene and 1-octen-3-ol in breads. Sensory tests showed the best appreciation scores for the breads produced with flour and pistachio powder. Highlights: Pistachio powder did not affect the numerical development of the starter culture. MySeq Illumina identified Lactobacillus as dominant LAB genus in almost all trials. Pistachio powder influenced the firmness but not the height of the breads. Lysine content increased consistently in pistachio supplemented breads. Pistachio breads reached the highest scores for the overall appreciation